Bacillus and fluorescent Pseudomonas from the rizosphere of wild agaves antagonists against pectinolytic bacteria - García-Martínez, Dulce Cecilia; Vázquez-López, Alfonso; Ayala-Escobar, Victoria; Nava-Díaz, Cristian; Aranda-Ocampo, Sergio (Ecosistemas y Recursos Agropecuarios, 2022)
Fluorescent Pseudomonas and Bacillus spp. are among the bacteria with the greatest potential for the biological control of plant diseases. The objectives of this research were: i) to identify fluorescent Pseudomonas and Bacillus species from the rhizosphere of wild agaves antagonists of pectinolytic bacteria, and ii) to detect the presence of genes for the biosynthesis of antimicrobial lipopeptides (AMPs) in the antagonist strains. The in vitro antagonist efficiency index (IEA) of 109 strains of fluorescent Pseudomonas and 119 of Bacillus spp. isolated from the rhizosphere of wild agaves against five pectinolytic bacterial strains of the genera Pectobacterium and Dickeya were evaluated. By PCR, antagonistic bacteria were identified by sequencing the 16S rRNA gene and AMPs genes: fenD (fengicin), ituC (iturin), srfAA (surfactin), and bmy (bacillomycin) for Bacillus spp., prnD (pyrrolnitrin), and phlD (2,4-diacetiylphloroglucinol) for fluorescent Pseudomonas were detected with specific primers. The in vitro IEA resulted in the selection of 25 antagonist strains against one or more pectinolytic bacteria. Comparison of the 16S rRNA gene sequences identified 11 (44%) strains in the Bacillus genus and 14 (56%) in Pseudomonas with similarities between 97 and 100%. Among the Bacillus and Pseudomonas species, most harbored between two to four AMPs genes. The ItuC, srfAA, and phlD genes were more frequent in all antagonist strains; all the genes evaluated were detected in the Bacillus subtilis (9B14) and Pseudomonas fluorescens (G3, D4, and H6) strains.